1993
DOI: 10.1111/j.1570-7458.1993.tb01716.x
|View full text |Cite
|
Sign up to set email alerts
|

The responses of the cabbage seed weevil (Ceutorhynchus assimilis) to the odour of oilseed rape (Brassica napus) and to some volatile isothiocyanates

Abstract: The responses of the cabbage seed weevil, Ceutorhynchus assimilis Payk. (Coleoptera: Curculionidae) to volatiles from oilseed rape (Brassica napus L.) were tested using a linear track olfactometer. Weevils were attracted towards the odour of rape during a short period before diapause and for most of their postdiapause life. Odours from both the flowering and green parts of the plant were attractive, but the odour of a non-host plant (Bell& perennis L.) was not. An entrainment extract of flowering rape volatile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…Furthermore, the flowers exhibit many of the features of 'insectpollinated plants', including bright yellow petals and nectar as a reward, and they are visited by a great variety of insects, some of which have been reported to be attracted to the anthers. Bartlet et al (1993) found that the cabbage seed weevil, Ceutorhynchus assimilis (Paykull) is attracted to the odour from oilseed rape stamens, and anthers are an important cue for syrphid visitors to this crop (Brunel et al, 1994;Golding et al, 1999). Therefore, distinctive volatile cues emanating from oilseed rape anthers or pollen itself may attract these other insects as well as pollen beetles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the flowers exhibit many of the features of 'insectpollinated plants', including bright yellow petals and nectar as a reward, and they are visited by a great variety of insects, some of which have been reported to be attracted to the anthers. Bartlet et al (1993) found that the cabbage seed weevil, Ceutorhynchus assimilis (Paykull) is attracted to the odour from oilseed rape stamens, and anthers are an important cue for syrphid visitors to this crop (Brunel et al, 1994;Golding et al, 1999). Therefore, distinctive volatile cues emanating from oilseed rape anthers or pollen itself may attract these other insects as well as pollen beetles.…”
Section: Discussionmentioning
confidence: 99%
“…A linear track olfactometer (Sakuma & Fukami, 1985) adapted from Bartlet et al (1993) was used to examine the orientation responses of pollen beetles to oilseed rape floral odours. The olfactometer was made of transparent Perspex tubing within which two stainless steel rods were positioned to form a T-junction ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The cabbage seed weevil invades oilseed rape crops, the adults colonise flowering host plants and feed on pollen, and the larvae feed on the developing seeds before leaving the pods and pupating in the soil. The cabbage seedpod weevil (C. obstrictus) is native to Europe, and is a serious pest of brassicaceous oilseed crops in Europe and North America (Bartlet et al, 1993;Ferguson et al, 1999b;Ulmer and Dosdall, 2006;Valantin-Morison et al, 2007). The cabbage seedpod weevil is a small, dark grey "snout beetle" normally occurring after peak flowering and lays eggs in the pods of cruciferous plants.…”
Section: The Weevils (Ceutorhynchus Spp)mentioning
confidence: 99%
“…For example, host plant volatiles can regulate insect behaviors [2,3] . The volatiles of maize (Zea mays L.) are attractive to Western corn rootworm adults (Diabrotica virgifera) [4] , and the odour of oilseed rape (Brassica napus) attracts cabbage seed weevils (Ceutorhynchus assimilis) [5] . Moreover, non-host plants volatiles also can influence insect behaviors [6] ; Cymbopogon citrates, a plant with known repellent activity, has a repellent effect against mosquitos [7] , as do volatiles of the neem tree [8,9] .…”
Section: Introductionmentioning
confidence: 99%